2008
DOI: 10.1074/jbc.m705753200
|View full text |Cite
|
Sign up to set email alerts
|

Dimer-Oligomer Interconversion of Wild-type and Mutant Rat 2-Cys Peroxiredoxin

Abstract: Rat heme-binding protein 23 (HBP23)/peroxiredoxin (Prx I) belongs to the 2-Cys peroxiredoxin type I family and exhibits peroxidase activity coupled with reduced thioredoxin (Trx) as an electron donor. We analyzed the dimer-oligomer interconversion of wild-type and mutant HBP23/Prx I by gel filtration and found that the C52S and C173S mutants existed mostly as decamers, whereas the wild type was a mixture of various forms, favoring the decamer at higher protein concentration and lower ionic salt concentration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…Indeed, AhpC activity from several sources has been extensively studied and shown to hydrolyze peroxides in the absence of hemin (24,44,52). We found that AhpC variants with substitutions at the redox-active Cys 47 and Cys 165 positions, which are catalytically inactive and unable to form disulfide bridge between monomers (52), bound hemin like the native enzyme, indicating that hemin binding occurs independently of enzyme function or oligomerization.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, AhpC activity from several sources has been extensively studied and shown to hydrolyze peroxides in the absence of hemin (24,44,52). We found that AhpC variants with substitutions at the redox-active Cys 47 and Cys 165 positions, which are catalytically inactive and unable to form disulfide bridge between monomers (52), bound hemin like the native enzyme, indicating that hemin binding occurs independently of enzyme function or oligomerization.…”
Section: Discussionmentioning
confidence: 95%
“…AhpC is a 2-Cys peroxiredoxin that, when coupled with a disulfide reductase as an electron donor, acts on hydrogen peroxide, peroxynitrite, and organic hydroperoxides to generate their corresponding alcohols (24). Prxs are also implicated in regulatory functions, as mainly reported in eukaryotes, such as transcription, apoptosis, and cellular signaling (25)(26)(27).…”
mentioning
confidence: 99%
“…Both Cys 52 and Cys 173 are reactive cysteines in Prx I. Glutathionylation of these two cysteines will inhibit the peroxidase activity of Prx I. In addition, structural analysis of Prx from various species (36,37) (38) have reported that glutathionylation of plant 1-Cys Prx from Populus tremula, which exists in a very different structure with a subunit interface different from that reported for mammalian 2-Cys Prx (39), could induce the dissociation of this dimeric 1-Cys Prx.…”
mentioning
confidence: 99%
“…A large number of studies have demonstrated that the oxidation state of peroxidatic cysteine Cys P governs the quaternary structure of typical 2-Cys Prxs (1,28,48). However, protein self-polymerization is not coupled exclusively to redox transformations of cysteine residues because the composition of the surrounding solvent and post-translational modifications also condition the proportion of 2-Cys Prx allocated to different (error bars)) of three independent experiments illustrated in the top.…”
Section: Discussionmentioning
confidence: 99%